The Concept Of التوبة In Al-Qur’an And Its Application - Achmad Ramadhan (Universitas Islam Negeri Sumatera Utara Medan, 2021)
This paper is aimed to describe the most important concept dealing with the characteristics of human beings and the possibility to diminish the bad elements of characteristics , namely التوبة , and its application.An order to turn to Allah the Almighty in repentance is narrated many times in the Qur’anic verses, some takes the direct form, the command verbs, like توبوا and تب and some takes the different verb from التوبة , ااستغفرو, the other takes the narration form, like ان الله ىحب التوابىن و ىحب المتطهرىن .Some Qur’anic verses elaborate the accepted التوبة and the other elaborates the rejected التوبة by Allah .The writer is interested to write and analyze the Qur’anic verses dealing with التوبة because he wants to have full understanding dealing with التوبة in the al-Qur’an. The result of the writing is that the التوبة activities should consist of 4 principles, namely الندم على المعصىة ( Regret for doing crime ); و الاءقلاع عنها (To be away from doing crime or evil); الاءستغفار (Asking for forgiveness) and العزم على عدم العودة الىها (A wish not do the same crime or evil in the other moment). By having these 4 (four) conditions of التوبة , Allah the Almighty may accept the التوبة . Conversely, without having them, the التوبة will be rejected